Pendampingan corak geometris dengan teknik sulam sebagai sumber belajar usaha busana - Suciati Suciati; Astuti Astuti; Pipin Tresna Prihatini; Mandhe Sekar Nurindah; Mutiara Annandara (Jurnal Abmas, 2024)
Creativity in female Islamic boarding school students can be fostered through mentoring in geometric pattern training with thread embroidery techniques. This activity is a unity between training female students on decorative pattern design techniques and thread embroidery techniques that can decorate Muslim wear products. This activity was carried out together with 50 female students of the Daruttakwien Islamic Boarding School, Bekasi Regency, Indonesia. Designing decorative patterns and thread embroidery techniques was carried out to improve skills, encourage creativity, introduce sources of decorative textile ideas, build economic independence, and promote Indonesian cultural heritage. The benefits include the development of creative industries in the Islamic boarding school environment, economic opportunities for female students, a better understanding of decorative design, and decorative innovation in Muslim wear designs. The activity method is a workshop, and the activity results show that participants have successfully designed simple geometric patterns, mastered basic embroidery techniques, and can produce unique works. This workshop activity helps increase interest in embroidery art and inspires participants to continue practicing and developing creativity in embroidery art. Therefore, it can be concluded that this activity succeeded in creating an enthusiastic and productive learning atmosphere for female students, increasing the knowledge and skills of female students as participants in the field of embroidering geometric patterns on Muslim wear.   Abstrak Kreativitas pada santriwati pondok pesantren dapat dibina melalui pendampingan pelatihan corak geometris dengan teknik sulam benang. Kegiatan ini merupakan kesatuan antara melatih santriwati mengenai teknik mendesain corak dekoratif dan sulam benang teknik ini dapat menghiasi produk muslimah wear. Kegiatan ini dilakukan bersama dengan santriwati Pondok Pesantren Daruttakwien, Kab. Bekasi, Indonesia yang berjumlah 50 orang. Kegiatan mendesain corak dekoratif dan sulam benang teknik ini dilakukan dengan tujuan untuk meningkatkan keterampilan, mendorong kreativitas, memperkenalkan sumber ide dekoratif tekstil, membangun kemandirian ekonomi, mempromosikan warisan budaya Indonesia. Manfaat diantaranya pengembangan industri kreatif di lingkungan pondok pesantren, peluang ekonomi bagi santriwati, pemahaman yang lebih baik mengenai desain dekoratif, inovasi dekoratif dalam desain muslimah wear. Metode kegiatan bersifat workshop dan hasil kegiatan menunjukkan bahwa peserta berhasil mendesain corak geometris sederhana, menguasai teknik dasar menyulam dan dapat menghasilkan karya yang unik. Kegiatan workshop ini dirasakan sangat bermanfaat dalam meningkatkan minat terhadap seni sulaman dan menginspirasi untuk terus berlatih dan mengembangkan kreativitas dalam seni sulaman. Oleh karena itu, dapat disimpulkan bahwa kegiatan ini berhasil menciptakan suasana belajar yang antusias dan produktif dari santriwati, meningkatkan pengetahuan dan keterampilan santriwati sebagai peserta dalam bidang menyulam corak geometris pada muslimah wear. Kata Kunci: corak geometris; pakaian muslimah; teknik sulam